Mechanistic Differences in the Membrane Activity of Bax and Bcl-xL Correlate with Their Opposing Roles in Apoptosis - Bleicken, Stephanie (The Biophysical Society, 2013)
Based on their membrane-permeabilizing activity in vitro, it has been proposed that Bax-like proteins induce cytochrome c release during apoptosis via pore formation. However, antiapoptotic Bcl-2 proteins, which inhibit cytochrome c release, also display pore activity in model membranes. As a consequence, a unified description that aligns the pore activity of the Bcl-2 proteins with their apoptotic function is missing. Here, we studied the mechanism of membrane binding, oligomerization, and permeabilization by pro- and antiapoptotic Bcl-2 members at the single-vesicle level. We found that proapoptotic Bax forms large, stable pores via an all-or-none mechanism that can release cytochrome c. In contrast, antiapoptotic Bcl-xL induces transient permeability alterations in pure lipid membranes that have no consequences for the mitochondrial outer membrane but inhibit Bax membrane insertion. These differences in pore activity correlate with a distinct oligomeric state of Bax and Bcl-xL in membranes and can be reproduced in isolated mitochondria. Based on our findings, we propose new models for the mechanisms of action of Bax and Bcl-xL that relate their membrane activity to their opposing roles in apoptosis and beyond.